2014
DOI: 10.1073/pnas.1415191111
|View full text |Cite|
|
Sign up to set email alerts
|

Individual differences in the peripheral immune system promote resilience versus susceptibility to social stress

Abstract: Significance Depression and anxiety have been linked to increased inflammation. However, we do not know if inflammatory status predates onset of disease or whether it contributes to depression symptomatology. We report preexisting individual differences in the peripheral immune system that predict and promote stress susceptibility. Replacing a stress-naive animal’s peripheral immune system with that of a stressed animal increases susceptibility to social stress including repeated social defeat stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
506
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 575 publications
(575 citation statements)
references
References 45 publications
40
506
0
9
Order By: Relevance
“…Similar findings have been described in rodents (Avitsur et al, 2006;Brenhouse and Thompson, 2015;Hennessy et al, 2010b). Furthermore, early-life immune activation has been linked to greater neuroendocrine activation in the context of subsequent stressors (Shanks et al, 1995(Shanks et al, , 2000, and higher baseline levels of inflammation have been associated with greater stressinduced responses in animal models (Hodes et al, 2014) and humans (Eraly et al, 2014;Michopoulos et al, 2015). On the other hand, there is initial evidence that genes coding for pro-inflammatory cytokines could moderate the effect of childhood trauma on brain function.…”
Section: Synergysupporting
confidence: 63%
See 1 more Smart Citation
“…Similar findings have been described in rodents (Avitsur et al, 2006;Brenhouse and Thompson, 2015;Hennessy et al, 2010b). Furthermore, early-life immune activation has been linked to greater neuroendocrine activation in the context of subsequent stressors (Shanks et al, 1995(Shanks et al, , 2000, and higher baseline levels of inflammation have been associated with greater stressinduced responses in animal models (Hodes et al, 2014) and humans (Eraly et al, 2014;Michopoulos et al, 2015). On the other hand, there is initial evidence that genes coding for pro-inflammatory cytokines could moderate the effect of childhood trauma on brain function.…”
Section: Synergysupporting
confidence: 63%
“…On the one hand, different lines of research suggest that antiinflammatory strategies could prevent the onset of clinical outcomes. First, higher baseline levels of inflammation have been associated with greater stress-induced responses in animal models (Hodes et al, 2014) and humans (Eraly et al, 2014;Michopoulos et al, 2015). Second, administration of anti-inflammatory agents, such as COX-2 inhibitors or IL-10, can buffer the expression of biological and clinical sequelae of early-life stress in rodents, including the reduction in prefrontal cortex parvalbumin levels and the onset of depressive-like symptoms (Brenhouse and Andersen, 2011b;Wieck et al, 2013).…”
Section: Reversibilitymentioning
confidence: 99%
“…Inflammation is also implicated in these psychiatric disorders (6)(7)(8)(9)(10)(47)(48)(49)(50). Recent studies showed that peripheral IL-6 is critical in regulating stress-related depression-like phenotypes in rodents (51)(52)(53). Because sEH plays an active role in the inflammatory response (18)(19)(20), it is possible that increased levels of sEH protein in the parietal cortex may play a role in the pathogenesis of these psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have shown that individual differences in peripheral immune responses (IL-6 responses, in particular) are associated with the susceptibility of laboratory animals to social avoidance after repeated social defeat stress. This susceptibility to social avoidance can be reversed following peripheral administration of a monoclonal antibody to IL-6 that also does not cross the BBB (Hodes et al, 2014(Hodes et al, , 2015. Conversely, overexpression of IL-1 receptor antagonist in the brain blocked chronic stress-induced anhedonia as well as impairment in hippocampal neurogenesis, a primary mechanism through which chronic stress is believed to induce depression Goshen et al, 2008).…”
Section: Immunological Mechanismsmentioning
confidence: 99%